Implementation of Cambridge Curriculum in Islamic Elementary Schools: Pelaksanaan Kurikulum Cambridge di Sekolah Dasar Islam - ‘Akifan, Muhammad ‘Alin; Hidayatulloh, Hidayatulloh (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Curriculum development is a key factor in improving the quality of education, particularly in Islamic schools that are adapting to global standards. Specific Background: The Cambridge Curriculum has been adopted in several Islamic schools in Indonesia to enhance learning outcomes and align with international benchmarks. Gap: However, limited studies have explored how this curriculum is implemented in Islamic contexts, especially in relation to challenges faced by schools. Aim: This study aims to describe the implementation of the Cambridge Curriculum in an Islamic elementary school and identify the obstacles encountered. Results: The findings reveal that while the curriculum introduces modern teaching strategies and enriches learning experiences, its implementation is hindered by limited teacher capacity, insufficient resources, and difficulties in student adaptation. Novelty: This study highlights the integration of an international curriculum with Islamic values, offering insights into contextual adaptation in local educational settings. Implications: The results provide practical recommendations for policymakers and school administrators in managing curriculum innovation, while contributing to the academic discourse on curriculum globalization in Islamic education. Highlights: Adoption of Cambridge Curriculum in Islamic schools Challenges in teacher capacity and resources Integration of global curriculum with local Islamic values KeywordCambridge Curriculum; Islamic education; Curriculum implementation; Teacher capacity; Student adaptation